Chocolat - Brown, David, 1916-2010.; Golden, Kit.; Holleran, Leslie; Jacobs, Robert Nelson; Hallstrm̲, Lasse; Binoche, Juliette, 1964-; Dench, Judi, 1934-; Molina, Alfred, 1953-; Olin, Lena.; Depp, Johnny; Harris, Joanne, 1964-; Miramax Films; et al. ([United States] : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2001)
When a single mother and her young daughter move to rural France and open a chocolate shop - with Sunday hours - across the street from the local church, they are met with some resistance from the rigidly moral community. But as soon as the townspeople discover their delicious products, their attitudes begin to change.
Based on the novel by Joanne Harris.
Special features: The making of Chocolat featurette ; commentary with director Lasse Hallstrm̲ and producers David Brown, Kit Golden and Leslie Holleran ; the costumes of Chocolat ; production design featurette ; deleted scenes.
Director of photography, Roger Pratt ; editor, Andrew Mondshein ; music, Rachel Portman ; costume designer, Reně Ehrlich Kalfus ; production designer, David Gropman.
Juliette Binoche, Judi Dench, Alfred Molina, Lena Olin, Johnny Depp.
DVD, widescreen presentation; Dolby Digital.
English or French language soundtrack with optional Spanish ; closed-captioned in English for the hearing impaired.
Keywords: Single mothers -- France -- Drama; Chocolate -- France -- Drama; Lent -- France -- Drama; Cities and towns -- France -- Drama; Feature films; Video recordings for the hearing impaired